Hexane Extract from Squirrel-Tail Palm Fruit (Wodyetia bifurcata) as a Moisturizing Cream: Phytochemical Profile, Formulation, and Evaluation - Rosnani Nasution; Fahzir Zahwari; Muhammad Bahi; Reza Akbar Bastian; Marianne Marianne (Malacca Pharmaceutics, 2026)
Dry skin, characterized by excessive water loss from the outermost layer of the epidermis, is a common dermatological concern that can be addressed with topical moisturizers. This study aimed to formulate and evaluate a moisturizing cream based on the n-hexane extract of squirrel-tail palm fruit (Wodyetia bifurcata) and to identify its phytochemical profile. The dried fruit pulp was macerated in n-hexane, and the resulting extract was characterized using gas chromatography–mass spectrometry (GC–MS). Two cream formulations containing 5% (F1) and 15% (F2) of the extract, together with a base cream (F0) and a commercial cream (F+), were prepared as oil-in-water emulsions and evaluated for moisturizing effectiveness on the heels of six female volunteers (aged 35–50) over 14 days using a skin moisture analyzer. Physical properties of the creams were assessed using organoleptic, homogeneity, pH, spreadability, adhesion, irritation, and hedonic tests, along with a four-cycle stability test. GC–MS analysis identified 48 compounds dominated by fatty acids and their methyl esters, with 9-octadecenoic acid (Z)-, methyl ester (10.55%), I-(+)-ascorbic acid 2,6-dihexadecanoate (8.14%), and hexadecanoic acid, methyl ester (5.55%) as major constituents. The mean moisturizing effectiveness values were 13.46% for the crude extract, 19.48% for F1, and 25.83% for F2, indicating concentration-dependent moisturizing activity. All physical property results complied with the SNI 16-4399-1996 standard, and no skin irritation was observed. Overall, formulation F1 was identified as the optimal preparation in balancing physical stability, sensory acceptability, and moisturizing performance, supporting the cosmetic potential of W. bifurcata fruit as a natural moisturizing agent.